Reglamentacja dostępu do pasa drogowego a koszty przełożenia sieci na drogach publicznych - Sobieralski, Krzysztof (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
Traffic lanes, as one of the components of public property, are subject to special protection, which is expressed in the regulation of their use for purposes other than road management or road traffic. An example of this regulation is the need to obtain a permit to occupy a traffic lane, that is, to repeal the general prohibition in an individual case. However, an entity with the appropriate permit to occupy a traffic lane does not have full rights to this public asset, but only the so-called right to someone else’s thing. This has a number of practical consequences.
Keywords: traffic lane; regulation; permit to occupy a traffic lane